2020
DOI: 10.5812/jcrps.107580
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Performance Indicators of Educational Hospitals Affiliated with Kermanshah University of Medical Sciences Before and After the Implementation of Healthcare Reform Plan

Abstract: Background: The most important factor representing the performance and utilization of hospital services are hospital indicators. Objectives: The aim of study was comparison performance indices before and after health reform plan in Kermanshah and compared with the standard of the Iranian Ministry of Health. Methods: the study was comparative and descriptive-analytical that performed cross-sectional in 2017 and conducted in seven educational hospitals in Kermanshah. The data were related to 37 indices in five a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…However, literature shows mixed results in Iran. A study by Cheshmekaboodi et al indicated that implementation of the HESP has had a positive association with EDVs ( 13 ). On the contrary, Emamgholipour et al in Tehran found that implementation of the HSEP had no significant effect on the rate and trend of indices such as EDVs and percentage of patients discharged against medical advice ( 11 ).This intervention had a positive effect on the rate and trend of the average response time for emergency tests ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, literature shows mixed results in Iran. A study by Cheshmekaboodi et al indicated that implementation of the HESP has had a positive association with EDVs ( 13 ). On the contrary, Emamgholipour et al in Tehran found that implementation of the HSEP had no significant effect on the rate and trend of indices such as EDVs and percentage of patients discharged against medical advice ( 11 ).This intervention had a positive effect on the rate and trend of the average response time for emergency tests ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…Factors such as type of hospital (general or specialized hospital), hospital function (teaching hospital, acute care facility, long-term hospital, etc. ), hospital size, and the ratio of specialist physicians to health professionals may affect the outcome of HSEP in emergency departments (13)(14)(15). Also, EDVs can be influenced by various factors, such as population demographics, healthcare infrastructure, and health policies.…”
Section: Discussionmentioning
confidence: 99%